Relocatable Classrooms. Educational Facilities Review Series Number 10 - Baas, Alan M.; ERIC Clearinghouse on Educational Management ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Because of structural or financial limitations, many existing school buildings cannot be rebuilt to accommodate the flexible space requirements of such innovations as open plan teaching, individualized instruction, or modular scheduling. Schools with such buildings can keep pace with educational change by using relocatables. At the present time, there are few documents on relocatable units; more can be expected as educators explore the possibilities such units suggest for solving temporary space needs. The literature reviewed here reflects the contemporary emphasis on variable learning spaces and suggests a number of creative uses for temporary structures. To gather the documents in this review, Research in Education and Current Index to Journals in Education monthly catalogs were searched from January 1968 through September 1972. (Author)
Sponsoring Agency: National Center for Educational Research and Development (DHEW/OE), Washington, DC.
Contract Number: OEC-0-8-080353-3514.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Building Design; Cost Effectiveness; Design Requirements; Educational Facilities; Facility Planning; Flexible Facilities; Literature Reviews; Mobile Classrooms; Prefabrication; Relocatable Facilities; School Expansion; Space Utilization